ENSINO DE CIÊNCIAS NAS ESFERAS DA EDUCAÇÃO BÁSICA: CONTRIBUIÇÕES DE UM DOCUMENTO ARTICULADOR PARA A PRÁTICA DOCENTE - Ehle, Cristiane Suzana Langbecker (2024)
The study is part of the line of research on Teacher Training in Science and Mathematics, in the Graduate Program in Science and Mathematics Teaching at the Franciscan University. A document with some guidelines, present in official documents, for teaching Science was developed to be used by educators and other professionals in the field of education. The aim is to contribute to teaching practice in the area of Paraíso do Sul, a city located in the state of Rio Grande do Sul. To achieve this, it was necessary to examine the official documents that guide Education at the national, state and city levels, as well as understand how Science teaching is present in official teaching documents in Basic Education. Thus, a documentary and descriptive analysis was carried out on documents such as the Law of Guidelines and Bases, Federal Constitution, National Common Curricular Base, Gaúcho Curricular Reference, Municipal Guiding Document of Paraíso do Sul, National Education Council, State Education Council, City Education Council and some scientific articles. Upon articulating the information and the establishment of science teaching dialogues between the aforementioned documents, which guide the educational work, a single document was created with some contributions from science teaching to the educational scenario. The study and research were based on the organization of the aforementioned material, which are available on virtual platforms in the city of Paraíso do Sul. Those documents cover the teaching of Science and the attributions of each sphere of Basic Education in order to bring teachers and school managers a broad and evolved vision, since updating these professionals is essential for improving the way they pass on their knowledge to students and their commitment to the classes in which they work. A constant transformation of the educational scenario must be promoted. Therefore, educators who acquire new knowledge and have diverse materials and resources are able to make students feel more encouraged, having satisfaction and pleasure in their educational trajectory.